The impact of collaborative writing on ESL students' writing skills / Katherine Livan Kehing - Kehing, Katherine Livan (Faculty of Education, 2010)
Collaborative writing is not something new in the education system. It has been practiced by teachers and educators since long time ago. The use of collaborative writing has also proven to help students to improve on their writing. There are many ways in practicing collaborative writing that can be effectively used on teaching writing. Collaborative writing could help students to improve on their academic performances, social skills, as well as preparing students for lifelong learning skills. However, there is a lack of awareness on how effective a collaborative task could be. Educators seem to take collaborative tasks for granted and ignore its effects on students especially those who are poor in English language. There is also less reflection towards collaborative writing and how it could help improve students' writing. Therefore, this study aims to identify the effective ways in using collaborative writing, to investigate the effectiveness of collaborative writing, and to explore the current and near future impact of collaborative writing method in the classroom. A total of 50 Form 3 respondents from SMK Marudi, Baram, Sarawak were selected for this study. The findings ofthis study show that students portrayed positive attitudes towards collaborative tasks and gained a lot of benefits when working collaboratively.